Measuring social relationships in different social systems: the construction and validation of the Evaluation of Social Systems (EVOS) scale - Aguilar-Raab, Corina; Grevenstein, Dennis; Schweitzer, Jochen (PLOS ONE, 2015)
Social interactions have gained increasing importance, both as an outcome and as a possible mediator in psychotherapy research. Still, there is a lack of adequate measures capturing relational aspects in multi-person settings. We present a new measure to assess relevant dimensions of quality of relationships and collective efficacy regarding interpersonal interactions in diverse personal and professional social systems including couple partnerships, families, and working teams: the EVOS. Theoretical dimensions were derived from theories of systemic family therapy and organizational psychology. The study was divided in three parts: In Study 1 (N = 537), a short 9-item scale with two interrelated factors was constructed on the basis of exploratory factor analysis. Quality of relationship and collective efficacy emerged as the most relevant dimensions for the quality of social systems. Study 2 (N = 558) confirmed the measurement model using confirmatory factor analysis and established validity with measures of family functioning, life satisfaction, and working team efficacy. Measurement invariance was assessed to ensure that EVOS captures the same latent construct in all social contexts. In Study 3 (N = 317), an English language adaptation was developed, which again confirmed the original measurement model. The EVOS is a theory-based, economic, reliable, and valid measure that covers important aspects of social relationships, applicable for different social systems. It is the first instrument of its kind and an important addition to existing measures of social relationships and related outcome measures in therapeutic and other counseling settings involving multiple persons.